Mental qualities and employed mental techniques of young elite team sport athletes - Holland, M. J. G.; Woodcock, C.; Cumming, J.; Duda, J. L. (Journal of Clinical Sport Psychology, 2010)
Research on the psychological characteristics of elite performers has primarily focused on Olympic and World champions; however, the mental attributes of young developing and talented athletes have received less attention. Addressing this, the current study had two aims: (a) to examine the perceptions held by youth athletes regarding the mental qualities they need to facilitate their development and (b) to investigate the mental techniques used by these athletes. Forty-three male youth rugby players participated in a series of focus groups. Inductive content analysis revealed 11 categories of psychological qualities, including enjoyment, responsibility, adaptability, squad spirit, self-aware learner, determination, confidence, optimal performance state, game sense, attentional focus, and mental toughness. Techniques employed included personal performance strategies, reflection on action, taking advantage of a supportive climate, and team-based strategies. Findings are discussed in relation to their implications for mental skills training program development and evaluation in the case of youth elite team sport athletes.